1997
DOI: 10.1016/s0022-5347(01)65370-9
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Dysfunction in Peyronie's Disease: An Analysis of 222 Patients Without Previous Local Plaque Therapy

Abstract: Sexual dysfunction was evaluable in 31.5% of patients, and the main cause of impotence and loss of erection was veno-occlusive dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
68
0
12

Year Published

2001
2001
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(84 citation statements)
references
References 14 publications
4
68
0
12
Order By: Relevance
“…3,15 Localized penile induration is equivalent to scar formation and leads in the majority of cases to penile curvature during erection. At least 30%, 20 and in our series 40.8% of those with Peyronie's disease suffer from erectile dysfunction because of pain or inability to achieve vaginal penetration.…”
Section: Epidemiology Of Peyronie's Disease F Sommer Et Alsupporting
confidence: 45%
“…3,15 Localized penile induration is equivalent to scar formation and leads in the majority of cases to penile curvature during erection. At least 30%, 20 and in our series 40.8% of those with Peyronie's disease suffer from erectile dysfunction because of pain or inability to achieve vaginal penetration.…”
Section: Epidemiology Of Peyronie's Disease F Sommer Et Alsupporting
confidence: 45%
“…In order to discriminate patients with and without ED, we divided the scores of the total scale into five comparable intervals. For the purpose of comparing our data to the data of Capelleri et al, 2 we adapted their diagnostically evaluated intervals indicating severe (sum score 1-10), moderate (11)(12)(13)(14)(15)(16), mildmoderate (17-21), mild (22-25) and no ED (26-30). Sensitivity, specificity and positive prediction were computed for optimal cutoff for the total scale and for the erectile function short scale.…”
Section: Discussionmentioning
confidence: 99%
“…11 In conformity with the standardized protocol used by our Peyronie's disease study group, a main inclusion criterion for the study was the evidence of a palpable dorsal penile plaque to define patients with Peyronie's disease. 12 Criteria for inclusion of all patients were (a) a stable heterosexual partnership and (b) at least one attempt of sexual intercourse over the last 4 weeks. The aetiology of ED included four patients with pure arteriogenic, four patients with venoocclusive, five patients with neurogenic, 10 patients with psychogenic, three patients with medical induced and 33 patients with mixed origin.…”
Section: Study Participantsmentioning
confidence: 99%
“…7,13,26 Sexual dysfunction is reported to be a part of presenting symptom complexes in 4 to 80% of Peyronie's patients in previously published series. 12,15 Although excessive angulation due to penile curvature, pain on erection, tenderness of the plaque and performance anxiety may all contribute to ED, it has been shown that penile vascular abnormalities are responsible for ED in 61 ± 70% of cases. 12,27 Veno-occlusive dysfunction (VOD) is reported to be present in 30 ± 86% and the role of arterial disease has also been shown in 44 ± 52% of Peyronie's patients with ED although it is not easy to determine the exact etiologic factor in every case.…”
Section: Discussionmentioning
confidence: 99%